Effects of the Fasting‐Postprandial State on Arterial Spin Labeling MRI‐Based Cerebral Perfusion Quantification in Alzheimer's Disease - Li, Runzhi; Zhuo, Zhizheng; Hong, Yin; Yao, Zeshan; Li, Zhaohui; Wang, Yanli; Jiang, Jiwei; Wang, Linlin; Jia, Ziyan; Sun, Mengfan; Zhang, Yuan; Li, Wenyi; et al. (Journal of magnetic resonance imaging, 2024)
Background The fasting‐postprandial state remains an underrecognized confounding factor for quantifying cerebral blood flow (CBF) in the cognitive assessment and differential diagnosis of Alzheimer's disease (AD). Purpose To investigate the effects of fasting‐postprandial state on arterial spin labeling (ASL)‐based CBF in AD patients. Study Type Prospective. Subjects Ninety‐two subjects (mean age = 62.5 ± 6.4 years; females 29.3%), including 30 with AD, 32 with mild cognitive impairment (MCI), and 30 healthy controls (HCs). Differential diagnostic models were developed with a 4:1 training to testing set ratio. Field Strength/Sequence 3‐T, T1‐weighted imaging using gradient echo and pseudocontinuous ASL imaging using turbo spin echo. Assessment Two ASL scans were acquired to quantify fasting state and postprandial state regional CBFs based on an automated anatomical labeling atlas. Two‐way ANOVA was used to assess the effects of fasting/postprandial state and disease state (AD, MCI, and HC) on regional CBF. Pearson's correlation analysis was conducted between regional CBF and cognitive scores (Mini‐Mental State Examination [MMSE] and Montreal Cognitive Assessment [MoCA]). The diagnostic performances of the fasting state, postprandial state, and mixed state (random mixing of the fasting and postprandial state CBF) in differential diagnosis of AD were conducted using support vector machine and logistic regression models. Statistical Tests Two‐way ANOVA, Pearson's correlation, and area under the curve (AUC) of diagnostic model were performed. P values <0.05 indicated statistical significance. Results Fasting‐state CBF was correlated with cognitive scores in more brain regions (17 vs. 4 [MMSE] and 15 vs. 9 [MoCA]) and had higher absolute correlation coefficients than postprandial‐state CBF. In the differential diagnosis of AD patients from MCI patients and HCs, fasting‐state CBF outperformed mixed‐state CBF, which itself outperformed postprandial‐state CBF. Data Conclusion Compared with postprandial CBF, fasting‐state CBF performed better in terms of cognitive score correlations and in differentiating AD patients from MCI patients and HCs. Evidence Level 2 Technical Efficacy Stage 3